INTEGRASI SISTEM AKADEMIK, PEMBAYARAN, DAN PERPUSTAKAAN BERBASIS WEB DI SMK ASSA’ADATUL ABADIYAH - Muhamad Sobri; Yunata Kandhias Akbar (LPPM Universitas Abdurrab, 2026)
Current data management procedures at SMK Assa'adatul Abadiyah face integrity and efficiency issues due to separate and manual processes. Academic processes, tuition payment recording, and library transactions operate independently using ledgers and Microsoft Excel, leading to data redundancy and delayed reporting. This study aims to design an integrated system connecting academic, payment, and library data to improve school management efficiency. The system was developed using the Rapid Application Development (RAD) method, emphasizing iterative development and user involvement, and modeled using the Unified Modeling Language (UML). The system is web-based, built using PHP and MySQL database. Black-box testing results indicate that all system functionalities, including the report card blocking mechanism for students with outstanding administration, performed 100% according to the scenarios. The implementation of this system successfully integrates data flow between work units, thereby minimizing redundancy and accelerating the reporting process.